(untitled) (Perner’s Contacts, 2015)
In preparation for the broader topic structure of logistics processes was research done. The research question was, if the choice of an independent central logistics department in a manufacturing company is in relation with the size of the manufacturing company or branch. The aim of this paper is to present some results of this research.